Use of virtual consultations in an orthopaedic rehabilitation setting: how do changes in the work of being a patient influence patient preferences? A systematic review and qualitative synthesis - Jeremy Jones; Carl R May; Anthony W Gilbert; Anju Jaggi (BMJ Open)
Objectives To systematically review qualitative studies reporting the use of virtual consultations within an orthopaedic rehabilitation setting and to understand how its use changes the work required of patients.Methods Following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement, we conducted a systematic review of papers to answer the research question ‘How do changes in the work of being a patient when using communication technology influence patient preferences?’ Electronic databases were searched for studies meeting the inclusion criteria in April 2020.Results The search strategy identified 2057 research articles from the database search. A review of titles and abstracts using the inclusion criteria yielded 21 articles for full-text review. Nine studies were included in the final analysis. Six studies explored real-time video conferencing and three explored telephone consultations. The use of communication technology changes the work required of patients. Such changes will impact on expectations for care, resources required of patients, the environment of receiving care and patient–clinician interactions. This adjustment of the work required of patients who access orthopaedic rehabilitation using communication technology will impact on their experience of receiving care. It is proposed that changes in the work of being a patient will influence preferences for or against the use of communication technology consultations for orthopaedic rehabilitation.Conclusion We found that the use of communication technology changes the work of being a patient. The change in work required of patients can be both burdensome (it makes it harder for patients to access their care) and beneficial (it makes it easier for patients to access their care). This change will likely to influence preferences. Keeping the concept of patient work at the heart of pathway redesign is likely to be a key consideration to ensure successful implementation.PROSPERO registration number CRD42018100896.